The specificity of philosophical discourse of prose T. Abdikov and H. Adibaev (Eurasian Journal of Philology Science and Education, 2016)
The article discusses the specifics of philosophical discourse works of two contemporary writers of Kazakhstan – T.Abdikov and H.Adibaev. One of its features is using the story line of «man in the mirror,» according to M. Bakhtin. It is argued that the presence of confessional motifs of existential nature, emphasizing border situations in the spiritual sphere of heroes leads to expansion of the surreal space. Results of the study showed that the analysis of discourse of the works of contemporary intellectual philosophical prose should be carried out through the dialogue of the national literary tradition of the «seeker of truth» and the achievements of the world literary process. A clearly expressed desire for the conceptualization of reality and the relationship of the past and the present distinguish the discourse of writers of Kazakhstan. The results of these observations convince that the clashes of «voices» at all levels of the text – story, fable and stylistics enable writers to carry out an explication of new meanings by relating them to already known, to clarify the relationship of the author and the reader as peer communicators and uncover hidden relationships in the space of contemporary culture.
Keywords: plot situation; philosophical discourse; author; confession; hero; literary tradition; motif; surreal.